SISI LAIN PEREMPUAN DALAM SOROTAN MEDIA; TINJAUAN TEORI KELOMPOK BUNGKAM (MUTED GROUP THEORY-MGT) - ta’in, Mus (Pusat Studi Gender dan Anak LPPM UIN Sunan Ampel Surabaya, 2013)
Conceptually, the purpose ofÂ journalism embodied in the editorial policy ofÂ the media. Unfortunately,contextually, the efforts to disseminate the values of gender equality and gender equity in editorial policy wasdefeated by the ideology of capitalism. The man who get benefit from patriarchal ideology has been used bycapitalism to work together to preserve the structure of unequal gender relations. Preservation in inequalityrelationship is not only made women increasingly subordinated, but also led to the subordination of womenby women themselves. This can be seen in advertising as evident from the position occupied by women, on theone hand, women are in affirming a tool of persuasion in the image of a product and on the other handwomen are consumers who consume the products of capitalism. In this aspect, communication put men as thecenter and women are only their/menâs shadow. Male dominance occupies all public spaces, from to be decisionmakers to choose main actors, to be placed in the front, to have lot of opportunities, and to have moreavailable time. If the whole issue places men as an actor and the most dominant owner access, the women arenot aware that they have been struck dumb.